Methods of Interaction of Local Government with Participants of Economic Development of Municipal Formations Subjects of Russian Federation - USTYUZHNA, Olga Nikolaevna; KHUSAINOVA, Svetlana Vasilievna (Journal of Advanced Research in Law and Economics; Vol 6 No 4 (2015): JARLE Volume VI, Issue 4(14), Winter 2015, 2017)
The work reveals the basic provisions of the municipal sector of economics. The issues of cooperation between local governments and other participants in the economic development of the municipality are regarded in detail. It also specifies the composition of the subjects participating in the economic development of municipal formations, their role in each category of subjects in the economy of municipal formations is also determined etc.